Opazovanje in vedenjski zemljevidi - Goličnik, Barbara (Urbani izziv, 2002)
The paper presents some methods from a current research that investigates the effectiveness of public urban open space in meeting spatial dimensions and human needs. It discusses research techniques in environmental and behaviouralresearch such as observation and behavioural mapping. Bechtel and associates describe observation as a method having five dimensions: behaviour,environment, time, observer and record of observation. A behaviouralmap is an observational tool for recording people's behaviour. Bothtechniques are used in a case study that looks at public urban open spacesin the Edinburgh city centre. Because this research is in progress, the article does not include results. It represents the use of the method and the developed tools used for this particular case, presents and comments on observation and it's recording in terms of an analytical tool in evaluating public urban open space. Public urban open space is seen as a complex phenomenon defined by the interplay of spatial and human dimensions, thereforethe introduction discusses some general objectives of public urban open space, with regard to use and users.
Keywords: Edinburg; Melle Stomp; mesto; prostor (sociologija); urbana sociologija; urbanism; urbanizem